Recent Trends In Renewable Energy Sector Of EU - Mammadli, Sabuhi; Bayramov, Tofiq (Acta Carolus Robertus, 2023)
The energy efficiency issue attracts everybody’s attention all over the world. It is strongly linked with the climate change problem, and a series of solutions and recommendations are offered and prepared to meet these challenges. Recent energy policies are aimed to achieve a gradual and successful transition from conventional energy sources to alternative ones. The main intention is to achieve energy efficiency alongside decreasing the impact of production on the environment. However, historical trends suggest that usually similar policies have been ostensible, as they have only caused an increase in the amount of total energy consumption, rather than to achieve the aforementioned aim. On the other hand, EU countries have addressed a number of approaches to grow renewable energy installations at the national level as well as addressing issues that have arisen during the deployment of renewable energy infrastructures in various nations.